PELATIHAN CLINIKAL INSTRUKTUR METODE PRESEPTOR DALAM PEMBELAJARAN KLINIK DI RUMAH SAKIT UMUM DAERAH TANAH ABANG JAKARTA - Royani Chairiyah; Widanarti Setyaningsih (Jurnal Abdi Insani, 2023)
In order for health professionals to educate themselves and provide high quality services to society, clinical learning is a key requirement. Role model clinical educators must promote effective clinical learning. To give students a realistic picture of hospital work, a clinical supervisor or Clinical Instructor (CI) is very important in the learning process. Clinical supervisors must receive training to increase their knowledge and preparation in carrying out the role and responsibility of guiding students. Clarifying the roles, responsibilities and obligations of clinical instructors in guiding students at the Tanah Abang Regional General Hospital (RSUD) is the goal of this Community Service (PKM). The majority of participants reported good training themes (63.4%), adequate punctuality (49.6%), good atmosphere (60.1%), good material completeness (70.6%), good service or management attitude good (61.6%), and good media or tools (57.2%). The good category consists of speakers with an average speaker score of 85.85. Evaluation of Participants' Understanding of Clinical Instructors With an increase in the average score of 24.04 between the pre-test and post-test, the average pre-test score was 62.08, and the post-test average score was 85.12. Activity evaluation measures the instructor's clinical expertise as well as their attitude or readiness to use the preceptorship approach. By participating in this exercise, Clinical Instructors can have a better understanding of hospital preceptorship procedures that they can apply to other practice areas.